(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
The present review offers comprehensive data on the roles of Peptidyl Arginine Deiminase 4 (PAD4) in various diseases, including rheumatoid arthritis (RA). PAD4, an enzyme responsible for converting arginine to citrulline, has been linked to the development of chronic inflammation. The current study is a narrative review to determine whether PAD4 is a potential therapeutic target for RA and other illnesses. We searched PubMed and Google Scholar for studies published before 2024. The potential therapeutic utility of PAD4 in various diseases such as cancer, miscarriage, multiple sclerosis, retinopathy, and RA is emphasized in the article. This paper explores the advancements in the development of small-molecule inhibitors and monoclonal antibodies targeting PAD4. It stresses the importance of conducting additional research to resolve specificity, safety, and sustained effectiveness concerns. The review emphasizes the need for a comprehensive approach to completely comprehend the varied attributes and potential therapeutic applications of PAD4.